Fluorescent sophorolipid molecular assembly and its magnetic nanoparticle loading: a pulsed laser process - Singh, Pradeep Kumar; Mukherji, Ruchira; Joshi-Navare, Kasturi; Banerjee, Abhik; Gokhale, Rohan; Nagane, Satyawan; Prabhune, Asmita; Ogale, Satishchandra (Green Chemistry, 2013)
We report realization of strong green fluorescence in a fully biocompatible highly spherical mesoscale molecular assembly of sophorolipid created by pulsed UV laser processing of a water-based dispersion of sophorolipid. Remarkably, the said fluorescence is totally absent in the original molecule of sophorolipid and is thus the property of the pulsed laser induced modifications in the molecule and the assembly. We have separately examined the consequences of laser irradiation for glucose and oleic acid components which form the sophorolipid. This fluorescence character appears to be driven by the oleic acid component while the assembly process is assisted by the glucose component. Importantly the laser synthesized mesostructures can be easily redispersed in an aqueous medium after being dried and can also be loaded with magnetic nanoparticles (magnetite) for inducing the hyperthermia effect.

From micron to nano-curcumin by sophorolipid co-processing: highly enhanced bioavailability, fluorescence, and anti-cancer efficacy - Singh, Pradeep Kumar; Wani, Kirtee; Kaul-Ghanekar, Ruchika; Prabhune, Asmita; Ogale, Satishchandra (RSC Advances, 2014)
Co-sonication of curcumin and acidic sophorolipid in aqueous solution is shown to lead to a dramatic enhancement of curcumin bioavailability through size reduction and encapsulation. The interaction between the two is studied and discussed based on optical absorption, photoluminescence, dynamic light scattering (DLS), zeta potential, FE-SEM, TEM, Infrared spectroscopy and X-ray diffraction measurements. The cytotoxicity effects of curcumin on breast cancer cell lines, MCF-7 and MDA-MB-231, are shown to be significantly enhanced by the formation of its complex with sophorolipid. The relative cytotoxicity of curcumin with its SL(A) complex is more due to the presence of the glucose moiety. The results further suggest that sophorolipid based formulations, which solubilize and nano-encapsulate curcumin after lipid digestion, show great potential for curcumin cell entry.

From micron to nano-curcumin by sophorolipid co-processing: highly enhanced bioavailability, fluorescence, and anti-cancer efficacy (vol 4, pg 60334, 2014) - Singh, Pradeep Kumar; Wani, Kirtee; Kaul-Ghanekar, Ruchika; Prabhune, Asmita; Ogale, Satishchandra (RSC Advances, 2015)